FASILITASI WORKPLACE SPIRITUALITY DALAM KEBERTAHANAN KINERJA PERGURUAN TINGGI AGAMA ISLAM SWASTA (PTAIS) (Study Kasus Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi) - Afandi, Irfan (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This article attempts to explain the sustainability of higher education quality through the facilitation of workplace spirituality. The quality of Islamic higher education is important for the survival of private institute. One instrument that can be used to sustaining the quality performance of Islamic private higher education is facilitation of spirituality in the workplace. This research takes the case study of the Ibrahimy Genteng Islamic Institute. Scope of Study on the sustainability of the quality performance of Islamic private higher education through workplace spirituality facilitation. This study will focus on four things, namely; content (c), process (p), context (x) and outcomes (o). In the content study, content refers to the values developed to improve quality performance. In the process study (process) how workplace spirituality is developed as an effort to maintain quality performance. The context study examines the factors that support the facilitation of workplace spirituality and the outcomes study focuses on the benefits obtained by both individuals and the organization. IAI Ibrahimy uses the values ​​found in Sufism in the form of Ikhlas, Istiqomah, Solidarity, kinship, deliberation, Istikhoroh prayer, and ahlu sunnah wal jamaah as the values ​​developed. Improvements in quality and quantity are the result of developing these values.